EVALUATION OF WATER QUALITY USING POLLUTION INDEX IN CIMANUK WATERSHED, INDONESIA - Andy Wibawa Nurrohman; M. Widyastuti; Slamet Suprayogi (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2019)
Land use is one of the macro parameters that affects water quality in a watershed. The Cimanuk watershed which is dominated by agricultural land use and settlements has encountered a decline in water quality. There are eight parameters including pH, TDS, TSS, Nitrate, Phosphate, Sulphate, BOD, and COD analyzed to evaluate water quality utilizing the Pollution Index (IP) method. This research has provided a clear understanding of the status of water quality in the Cimanuk watershed based on six monitoring points carried out at the start of the 2018 rainy season. Overall, the IP values obtained ranged from 2.05 to 5.96 with the lightly polluted category at points A, B, C, D, and E, while for point F it was in the moderately polluted category. The key parameters that have the most influence on water quality pollution are Nitrate, Phosphate, Sulphate from fertilization activities in agricultural land, while runoff from settlements contribute to increasing parameters of BOD and COD. These results can be beneficial for sustainable management of water and land resources in the Cimanuk watershed.